BBS7–SHH Signaling Activity Regulates Primary Cilia for Periodontal Homeostasis - Chang, Pi En; Li, Shujin; Kim, Hyun-Yi; Lee, Dong-Joon; Choi, Yoon Jeong; Jung, Han-Sung (Frontiers in Cell and Developmental Biology, 2021)
Objectives: Mechanical stimuli are essential for the maintenance of periodontal ligament (PDL) homeostasis. Despite several studies on atrophic changes in PDL due to occlusal hypofunction, the underlying mechanism is still unknown. Here, we aimed to explore the changes of gene expression in occlusal hypofunctional PDL and elucidate the related role in maintaining the PDL homeostasis. Methods: To investigate the transcriptomic difference between control and hypofunctional PDL tissue from patients, RNA sequencing was performed on 32 human teeth. The atrophic changes in PDL were evaluated by histological analysis. The effect of Bardet-Biedl syndrome 7 (BBS7) knockdown was evaluated by RT-qPCR, Wound healing assay, and Tubule formation assay. Results: We detected that the expression of BBS7 was downregulated in occlusal hypofunctional PDL through RNA-sequencing. Dynamic changes, including the number of periodontal ligament cells, alignment of collagen fibers, the diameter of blood vessels, appearance of primary cilia, and torturous oxytalan fibers, were observed following occlusal hypofunction. Furthermore, Sonic Hedgehog signaling (Shh) activity was closely associated with BBS7 expression in periodontal ligament cells. In addition, the cell migration and angiogenesis were also suppressed by BBS7 knockdown in vitro. Conclusion: We suggest that BBS7 plays an essential role in maintaining Shh signaling activity for PDL homeostasis.